NATIONAL SECURITY AND THE CHALLENGES OF THE 21ST CENTURY (Isagoge - Journal of Humanities and Social Sciences, 2022)
This paper is set to discuss the issues on Nigeria’s national security and ways of meeting the challenges of the 21's century. It therefore examined and assessed what it requires to achieve national security and suggest ways of improving her national Security for a better 21’s century. It was discovered that Nigeria’s security issues over the years have been wrongly defined, relegating the major factors that bring better security. This paper, therefore recommend that for a better national security attainment in the 21's century, both the conventional and grand strategic measures should be applied. The need for economic empowerment, good governance, advance science and technology, human and material resources development, etc., must be considered and used for alternative national security attainment.
Keywords: National Security; The Challenges of the 21st Century; Democracy; Nigeria